Reverse identification method for simultaneous estimation of thermal conductivity and thermal contact conductance of multilayered composites. (July 2021) - Guo, J.; Chen, X.N.; Qu, Z.G.; Ren, Q.L.
Highlights: Indirect method is raised to measure thermal conductivity of multilayered composite. Thermal conductivity and contact conductance are estimated simultaneously. Effects of thermal contact conductance and thermal conductivity are separated. Experimental measurement error of thermal conductivity is less than 2.4%. Abstract: Multilayered insulation composites are characterized by their light weight, low thermal conductivity (TC), and good wave permeability and are widely used as heat-insulating materials in aerospace engineering. The existing direct measurement standards and equipment are not applicable in high-temperature, high-radiation, and low-pressure environments for materials whose thermal conductivities are similar to that of air. Moreover, the thermal responses of a multilayered insulation composite to the same boundary conditions resulting from different operation environments are different as a result of its wave permeability and spectral selectivity. The effective TCs are different in different operation environments. There is inevitably a non-negligible thermal contact conductance (TCC) between the individual layers. Thus, it is important to measure the effective TC of a multilayered insulation composite under normal working conditions in different operating environments for the thermal design of the insulation layer. In this study, an indirect measurement strategy based on inverse problem analysis was proposed to simultaneously estimate the TC and TCC of a multilayered insulation composite. The conjugate gradient method was used for the parameter and function estimations of the TC and TCC. The accuracy and robustness of the proposed method were verified numerically and experimentally. The results of a heat-shielding experiment showed no more than a 2.4% deviation for the estimated TC and 11.5% deviation between the measured and estimated temperatures. This method may offer a strategy to measure the thermophysical properties of multilayered insulation composites in an operational environment for aerospace engineering. It can improve the TC measurement accuracy and provide the basis of the physical properties for the thermal insulation design of multilayered insulation composites for use in various operation environments.